Total Quality Management Approach and how it Affects the Institutional Performance a Case Study from the Kingdom of Bahrain - AlDeeb, Horiya; Samman, Adel Al; Sulaibeekh, Duaa Abdulla Ali (International Journal of Social and Administrative Sciences, 2019)
This paper aims to examine the impact of applying a Total Quality Management approach on the institutional performance of an industrial company in Bahrain. A total of 20 managers working at different levels in the company were surveyed through a specifically designed questionnaire, date collected of which were subject to the analysis using SPSS software. Findings revealed a significant relationship between applying the principles of TQM with its different dimensions such as Total quality oriented leadership, continuous improvement, empowering employees and focus on the production process, and the institutional performance dimensions, such as profitability, productivity, operating efficiency and level of customers’ satisfaction in the study company, with concentration on the principle of the production process. Findings also revealed a significant relationship between applying the dimensions of TQM and the dimensions of institutional performance in the study company that could be attributed to demographic variables, such as gender, age, qualifications, experience, and job position.